Stereotypes and motivation in language learning among learners of European languages / Larisa Nikitina - Nikitina, Larisa (2015)
In the field of applied linguistics the importance of exploring language learners’ stereotypes about the target language country, culture and native speakers has been recognized by scholars and practitioners. However, there is a dearth of studies that have explored stereotypes held by language learners in an Asian educational context. Also, while the available studies have focused on stereotype content a systematic investigation of representations about the target language country are lacking. This thesis addresses these gaps. It pursues two overriding aims: firstly to extend the existing research on stereotypes about the target language country held by language learners and secondly to demonstrate a rigorous approach to investigating the stereotypical representations. The specific objectives this thesis pursues are: (1) to examine the content and structure of the language learners’ stereotypes about the target language country; (2) to identify consensual stereotypes about the TL country held by the language learners; (3) to assess favourability and salience of the stereotypes about the TL country; and (4) to examine association between the language learners’ stereotypes and their motivation to learn the foreign language. To achieve the research objectives, this thesis adopts a concurrent mixed methods approach in which the mixing of the qualitative and quantitative strands occurs in a parallel manner in all stages of research. The research instrument contained both openended and closed-ended questions. The data were collected among the learners of European languages in the University of Malaya. In the qualitative strand of the analysis, the internal structure and salience of the stereotypical images were investigated. The findings revealed the presence of several pervasive and highly salient images about each of the target language countries. These images formed the consensual stereotypes. In the quantitative strand, the stereotypes’ favourability was assessed and the associations between stereotypes and motivation were examined. The results indicated that the students’ images about the target language country were predominantly positive. Also, the findings provided empirical evidence in support of the existence of an association between stereotypes and motivation to learn the foreign language, especially the integrative orientation. This thesis and its findings have theoretical, methodological and practical implications for the field of applied linguistics. From the theoretical perspective, it demonstrates how links can be established between the language learners’ stereotypes about the target language country and their language learning motivation. From the methodological angle, the thesis demonstrates how a mixed methods approach can contribute to stereotype research in applied linguistics. From the pedagogical perspective, knowledge of language learners’ stereotypes about the target language country can help language educators to make empirically-based decisions about teaching the cultural component of language programs.